Transient Changes in Brain Metabolites after Transcranial Direct Current Stimulation in Spastic Cerebral Palsy: A Pilot Study - Auvichayapat, Paradee; Aree-uea, Benchaporn; Auvichayapat, Narong; Phuttharak, Warinthorn; Janyacharoen, Taweesak; Tunkamnerdthai, Orathai; Boonphongsathian, Wuttisak; Ngernyam, Niran; Keeratitanont, Keattichai (Frontiers in Neurology, 2017)
Background: Muscle spasticity is a disability caused by pyramidal system damage. Standard treatment for muscle spasticity usually includes muscle stretching, but the treatment outcomes are still unsatisfactory. Anodal transcranial direct current stimulation (tDCS) in patients with muscle spasticity results in significant improvement of spastic tone (p < 0.001). However, the mechanism of action by which tDCS treatment affects spasticity is unclear. Our pilot study aimed to investigate the effect of anodal tDCS on brain metabolites in the left basal ganglia and ipsilateral primary motor cortex (M1) in children with spastic cerebral palsy (CP). Materials and Methods: This study consisted of three steps, namely a baseline evaluation, treatment period, and follow-up period. In the treatment period, the patients were given 20 min of 1 mA anodal tDCS over the left primary motor cortex (M1) for 5 consecutive days. The outcomes were compared between pre- and immediate post-treatment in terms of brain metabolites, Tardieu scales, and the quality of upper extremity skills test. Results: Ten patients with spastic CP were enrolled. After tDCS, there were significant increases in the ratio of the NAA/Cr (p = 0.030), Cho/Cr (p = 0.043), and mI/Cr (p = 0.035) in the basal ganglia and the Glx/Cr ratio in M1 (p = 0.008). In addition, improvements in the amount of spasticity and hand function were also observed (p = 0.028). Conclusion: Five consecutive days of anodal tDCS over M1 appeared to reduce the degree of spasticity and increase NAA, Cho, mI, and Glx. Increasing the sample size in studies including spastic CP patients undergoing tDCS is warranted in future.